Method and device for automatically establishing VTEP of VXLAN and storage medium - LI XIN; LI YUANZHENG; CHEN WEIJIN (2023)
The invention provides a method for automatically establishing a VTEP (VXLAN Tunnel End Point) of a VXLAN (Virtual eXtensible Local Area Network). Three layers of network switching equipment exist between VXLAN equipment; the transmitting end VXLAN equipment fills a destination address in an Ethernet message header of a VXLAN message as an MAC address of the three-layer network switching equipment during transmission, the message is transmitted to the three-layer network switching equipment, then the three-layer network switching equipment transmits the message to the receiving end VXLAN equipment, and after the receiving end VXLAN equipment receives the VXLAN message, the receiving end VXLAN equipment transmits the message to the receiving end VXLAN equipment. A source IP in an Ethernet message, a source IP of a VXLAN message and a source MAC address of the VXLAN message are bound as a VTEP, and when a receiving end VXLAN device encapsulates a VXLAN, the MAC address of a VXLAN tunnel node is determined accor